Identity and emotion of secondary English Teacher during Merdeka curriculum - Nur, Maulidia Rachmawati; Soliha, Adila Nuramalia (Linguistics and ELT Journal, 2024)
There has been limited attention to Language Teacher Identity in the context of curriculum change in Indonesia. Merdeka Curriculum is the latest innovation in solving Indonesia’s curriculum issues. Drawing upon the teacher identity theory, this qualitative case study examines how three English teachers engaged their emotion within curriculum change in Indonesia and how identity affected their teaching practices during the Merdeka Curriculum. Data were collected through in-depth interviews and closed-ended questions. Finding indicate that teachers experience a variety of emotions in response to the curriculum change, which are generated by teachers’ identity constructions. Furthermore, teacher knowledge, experience, and competence identity in the context of Merdeka Curriculum impact their teaching practice. This case study underscores the importance of government attention of effective teacher training strategy to ease the transition and enhance educational outcomes.